Moralitas Aborsi karena Kehamilan Remaja: Ditinjau dalam Perspektif Feminisme dan Sains - Putri, Yulita; Nurhuda, Abid (Kajian Psikologi dan Kesehatan Mental, 2023)
Purpose: The purpose of this study is to describe the Morality of Abortion Due to Teenage Pregnancy. Research methodology: The method used is literature study with a feminism and science approach, then the data is collected and a descriptive analysis is carried out and finally conclusions are drawn. Results: The results of the study show that the Morality of Abortion Due to Teenage Pregnancy when viewed from a feminist perspective tends to be in the pro choice group which gives full rights to women to terminate their pregnancies because they are worried about their future. their children and also physically which are still unstable and immature or stable. Meanwhile, if viewed from a scientific perspective, abortion can be carried out with certain conditions, such as a place for a license to practice, professional staff, condition of the fetus, counseling for women and affordable rates. Conclusions: The morality of abortion due to teenage pregnancy, from a feminist perspective, tends towards the pro-choice group, which gives women full rights to terminate their pregnancies due to concerns about their future, their children's future, and their physical condition, which is still unstable and immature/unstable. Limitations: The limitation of this study is that it only discusses the permissibility of abortion, there is no detailed explanation regarding the dangers of abortion Contribution: This research contributes to groups that allow abortion, even so the hope is that in the next study it can explain the dangers of abortion so that it is balanced in the spread of knowledge.